Analisis Kualitas Pelayanan terhadap Kepuasan Pasien Poli Gigi di UPTD Puskesmas Curahnongko Menggunakan metode Servqual - Sisil Wulandari; Harmawan Teguh Saputra; Hanif Hadinata Utama (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the effect of service quality on patient satisfaction in the dental clinic at the Curahnongko Community Health Center (UPTD) in Jember Regency using the SERVQUAL method. The research method used a quantitative approach with a descriptive and explanatory design. A sample of 125 respondents was selected using a purposive sampling technique. Data were collected through a questionnaire based on the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. Data were then analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS. The results showed that all dimensions of service quality had a positive and significant effect on patient satisfaction, both partially and simultaneously, with empathy as the most dominant factor. The conclusion of this study confirms that improving service quality across all SERVQUAL dimensions in an integrated and sustainable manner will increase patient satisfaction in the dental clinic at the Curahnongko Community Health Center (UPTD) in Jember Regency.   Keywords: Service Quality, Patient Satisfaction, Dental Clinic, Community Health Center